Implementation of a Decision Support System for Selecting the Best Clothing Brand Using the Website-Based TOPSIS Method - Sokid Sokid (GWS Tech Solution, 2025)
The rapid growth of the fashion market increases the number of available clothing brands, making it harder for consumers to select the best option under multiple criteria. This study develops a web-based decision support system for selecting the best clothing brand using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The criteria include price as a cost criterion and material quality, comfort, durability, and suitability as benefit criteria. Brand alternatives are evaluated on a 1–10 scale and processed through TOPSIS steps, including normalization, weighting, determining ideal solutions, computing distances to the positive and negative ideal solutions, and calculating the preference value (Ci). The ranking results indicate that Elizabeth (A6) achieves the highest preference score (Ci = 0.723779), thus recommended as the best brand. The proposed system supports criteria and alternative input, automated computation, transparent step-by-step calculations, and result export, enabling more objective and efficient decision-making.